Behind the killing fields : a Khmer Rouge leader and one of his victims - Chon, Gina; Sambath Thet, 1968- (Pennsylvania studies in human rights., 2010)
In recent history, atrocities have often been committed in the name of lofty ideals. One of the most disturbing examples took place in Cambodia's Killing Fields, where tens of thousands of victims were executed and hastily disposed of by Khmer Rouge cadres. Nearly thirty years after these bloody purges, two journalists entered the jungles of Cambodia to uncover secrets still buried there. Based on more than 1,000 hours of interviews with the top surviving Khmer Rouge leader, Nuon Chea, Behind the Killing Fields follows the journey of a man who began as a dedicated freedom fighter and wound up accused of crimes against humanity. Known as Brother Number 2, Chea was Pol Pot's top lieutenant. He is now in prison, facing prosecution in a United Nations-Cambodian tribunal for his actions during the Khmer Rouge rule, when more than two million Cambodians died. The book traces how the seeds of the Killing Fields were sown and what led one man to believe that mass killing was necessary for the greater good. Coauthor Sambath Thet, a Khmer Rouge survivor, shares his personal perspectives on the murderous regime and how some victims have managed to rebuild their lives. The stories of Nuon Chea and Sambath Thet collide when the two meet. While Thet holds Chea responsible for the death of his parents and brother, he strives for understanding over revenge in order to reveal the forces that destroyed his homeland in the name of creating utopia. In this age of suicide bombers and terror alerts, the world is still at a loss to comprehend the violence of zealots. Behind the Killing Fields bravely confronts this challenge in an exclusive portrait of one man's political madness and another's personal wisdom. Gina Chon is a reporter for the Wall Street Journal. Sambath Thet writes for the Phnom Penh Post.